Psychological capital, work well-being, and job performance - Nangov, Rizal; ., Sasmoko; Indrianti, Yasinta (International Journal of Engineering and Technology, 2018)
Performance as a multidimensional concept has become a very interesting variable to be studied especially in the viewpoint of positive psychology. This study aims to see the influence of Psychological Capital and Work Well Being as an element in the positive psychology of Job Performance. The research method used is a quantitative method with survey technique. The results showed that Psychological Capital had a positive and significant impact on Job Performance as well as Worl Well Being. These results are expected to contribute positively to human resource managers so that the measurement of performance can be done by considering the various multidimensional components that influence it. Â